What good is meaning in life? - Woodard, Christopher (Linkoeping University Electronic Press, 2017)
Most philosophers writing on meaning in life agree that it is a distinct kind of final value. This consensus view has two components: the ‘final value claim’ that meaning in life is a kind of final value, and the ‘distinctness claim’ that it is distinct from all other kinds of final value. This paper discusses some difficulties in vindicating both claims at once. One way to underscore the distinctness of meaning, for example, is to retain a feature of our pretheoretical concept of meaning in life, according to which the least possible quantity of meaning is meaninglessness. Unfortunately, this makes it harder to defend the claim that meaning is a kind of final value. On the other hand, revising the concept to allow for negative meaning renders meaning closer in structure to other kinds of final value, but also makes it harder to defend the distinctness claim. In light of these difficulties, the paper explores the prospects of a theory of meaning in life which departs from the consensus view by rejecting the final value claim. On such a view, the value of meaning in life is entirely instrumental.